Cationic Dye Degradation by means of an Efficient Photocatalyst promoted by Aluminum Oxide - Kinyas Polat (Hittite Journal of Science and Engineering, 2018)
A visible active magnetically separable two component MgFe2O4-Al2O3/Ag3VO4 photocatalyst was prepared in order to improve the catalytic activity of Ag3VO4 by utilizing Al2O3 NPs Al2O3 adsorbent. Catalyst was characterized by using Fourier Transform Infrared spectrometer FTIR . Photocatalytic activity of MgFe2O4Al2O3/Ag3VO4 was measured by methylene blue MB degradation under visible light illumination emitted from 105 W tungsten light bulb. UV-vis spectrophotometer was employed to follow and identify the MB degradation and kinetics. Results suggested a first order kinetic model for the degradation having rate constant k, 0.03252 min-1. The halflife of catalytic degradation was found as 21.3 min. The photocatalytic activity of the neat Ag3VO4 was also measured and compared with the MgFe2O4-Al2O3/Ag3VO4. It was observed that rate constant of the degradation obtained with Ag3VO4 was 0.01577 min-1 and its half life 43.9 min. This revealed that an approximately twofold increase attained by using efficient nano Al2O3 adsorbent. At the end of the reaction catalyst particles were removed easily from the aqueous solution by a magnet